Current and prospective situation of municipal solid waste final disposal in Mexico: a spatio-temporal evaluation - Rueda Avellaneda, Juan Felipe; Rivas García, Pasiano; Gómez González, Ricardo; Benitez Bravo, Reyes; Botello Álvarez, José Enrique; Tututi Ávila, Salvador (Elsevier, 2021)
Mexico, similarly to other developing countries, has planned landfilling as the central technology to manage municipal solid waste (MSW). In this research, the current and future situation of final disposal of MSW in Mexico was studied, focusing on the spatial and temporal evaluation of final disposal sites (FDS), landfill gas (LFG) emissions, and potential power generation in an 80-year horizon. Geographic information systems were applied for spatial evaluation. The Mexico LFG 2.0 model was used to estimate the LFG emissions in 1782 FDS in operation, considering statal MSW characteristics and local FDS features. The transition towards a MSW management system that is less dependent on final disposal was carried out via a sensitivity analysis of the reduction of FDS in LFG emissions, power generation, and greenhouse gases (GHG) emissions. The study estimated that Mexico had an LFG generation of 2298 Mm3 in 2020, where only 4.6% of FDS were suited for power generation, up to 2534 GWh y-1. This electricity can avoid the emission of 1.45 Mt CO2 , since fossil fuels are predominant in the Mexican power grid. The sensitivity analysis showed that suppressing MSW landfilling could reduce 1636 Mt CO2 eq over the period studied compared to the business-as-usual scenario. The power generation potential of LFG has been used scarcely (165 GWh y-1). Public policies may focus on proposing economic incentives and establishing conditions for a biogas market, increasing the number of SL that use LFG for energy purposes.